International Capital Inflow and Sub-Saharan African Economy: Does Capital Inflow Lead Growth? - Adebayo, Ajisafe Rufus; Oluwaseun, Okunade Solomon (Growth, 2020)
Sub-Sahara African (SSA) countries have become more integrated with the world economy since the early 1990s leading to a surge in international capital inflows, but have also experienced sporadic downfalls in their growth rates leading to instabilities in some macroeconomic variables. This paper examined the dynamic and causal relationship between economic growth and international capital inflow in SSA using data covering the period of 1990 to 2018. Through Structural Vector Autoregression (SVAR) impulse response and variance decomposition, the study found a positive relationship between growth and international capital inflow in SSA. It also found negative relationships between macroeconomic instability and economic growth; and macroeconomic instability and international capital inflow in SSA. In addition, through VAR Granger Causality or Block Exogeneity Wald Tests, the study found a unidirectional causal relationship running from growth to international capital inflow in SSA. The study also found that international capital inflow did not cause economic growth but economic growth attracts international capital inflows. Therefore, the study concluded that a buoyant and viable economy provides conducive business environment for international investors better than less viable economy. Thus, the study recommended that governments and policy makers in SSA should put in place policies that will promote economic growth to attract more international capital inflows which would augment the scarcely available domestic capital resources most especially in terms of knowledge, skills and other technological advancement, that would later translate into further economic growth in SSA region.